Implementasi Algoritma Probabilitas Symetric Dalam Mendiagnosa Penyakit Akibat Gangguan Gizi - Devi Risianti; Maryaningsih Maryaningsih; Jhoanne Fredricka (UNIVED Press, 2025)
This research aims to implementation the symetric probability algorithm in building an expert system to diagnose diseases due by nutritional disorders. Disturbances in nutritional balance can cause a person's performance in activities to be not optimal and can even cause diseases that will interfere with daily routines. The lack of knowledge and concern for nutritional balance in the body is the cause of the emergence of health problems, in addition to the difficulty of access to consult a doctor also causes people to be less concerned about nutritional balance disorders. To overcome these problems, it is necessary to build an expert system to help someone diagnose diseases due to nutritional disorders and solutions that can be done online so that it is expected to facilitate users. The implementation of symetric probability used in this expert system can provide diagnoses of nutritional disorders expressed as a percentage to measure the certainty value of a hypothesis against a fact of disease due to nutritional disorders experienced by adults. This expert system was built using PHP programming language and MySQL database. This expert system can be used as a tool that makes it easier for people to diagnose early symptoms of diseases due to nutritional disorders because it can be accessed online.